1970
DOI: 10.1136/adc.45.241.404
|View full text |Cite
|
Sign up to set email alerts
|

Breast Feeding in Kingston, Jamaica

Abstract: Grantham-McGregor, S. M., and Back, E. H. (1970). Archives of Disease in Childhood, 45, 404. Breast feeding in Kingston, Jamaica. A longitudinal study was carried out on 300 Kingston infants born at the University Hospital of the West Indies. The method of milk feeding and the reasons given by the mothers for beginning bottle feeding were recorded. Other factors influencing the incidence of breast feeding were examined. Complementing in hospital, maternal employment, improving socio-economic status, advertisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…This may be related to the working status of more highly educated women. A study conducted in Jamaica showed that more non‐working, than working, mothers were breast‐feeding at 6 months ( Grantham‐McGregor & Back 1970). All mothers in this study were out of school and were not working, therefore duration of breast‐feeding was not affected by ongoing educational or job pursuits.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the working status of more highly educated women. A study conducted in Jamaica showed that more non‐working, than working, mothers were breast‐feeding at 6 months ( Grantham‐McGregor & Back 1970). All mothers in this study were out of school and were not working, therefore duration of breast‐feeding was not affected by ongoing educational or job pursuits.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding patterns show dissimilarities among cultures and different socio-economic strata (9). A number of cross-sectional studies concerned with breastfeeding have been conducted in Pakistan and elsewhere (10)(11)(12). Most of these studies have provided only limited information.…”
mentioning
confidence: 99%
“…Enquanto alguns autores 8,26 demonstraram que a idade materna não está associada à decisão da mãe em amamentar ou não, outros 11,16 encontraram relação direta entre as idades das mães e o tempo de amamentação.…”
Section: Resultsunclassified